Foreign bank and banking stability in Africa: does strong and weak corporate governance systems under different regulatory regimes matter? - Kusi, B.A.; Agbloyor, E.K.; Abor, J.; Simplice, A.A. (Journal of Financial Economic Policy, 2021)
Purpose: The purpose of this paper is to examine the effect of foreign bank assets (FBA) and (FBP) presence is examined in terms of banking stability in the economies with strong and weak country-level corporate governance (CLCG) in Africa between 2006 and 2015. Design/methodology/approach: Using a Prais-Winsten panel data model of 86 banks in about 30 African economies: findings on how FBA and presence influence banking stability in strong and weak corporate governance economies under different regulatory regimes are reported for the first time in Africa. Findings: The findings show that foreign bank presence (FBP) and assets promote banking stability. However, the positive effect of FBA and presence is enhanced in economies with strong CLCG, whereas the positive effect of FBA and presence is weakened in economies with weak CLCG. After introducing different regulatory regimes, it is observed that the enhancing effect of FBP and assets on banking stability in the full sample and economies with strong and weak CLCG systems are deepened or improved under the loan loss provisional regulation regime. However, under the private and public sector-led financial transparency regulations, the reducing effect of FBP and assets on banking stability in economies with weak corporate governance systems is further dampened. Practical implications: These findings show that the relationship between FBP and assets is deeply shaped by corporate governance systems and regulatory regimes in Africa. Hence, policymakers must build strong corporate governance and sound regulatory regimes to enhance how foreign bank operations promote banking stabilityOriginality/value – This study presents first-time evidence on how FBA and presence influence banking stability under strong and weak governance systems while considering different regulatory regimes.
Research Article
Keywords: Financial markets and institutions; Economics of regulation; Stability